Neighborhood walkability and cardiometabolic risk factors in australian adults: An observational study - Müller-Riemenschneider, F.; Pereira, Gavin; Villanueva, K.; Christian, H.; Knuiman, M.; Giles-Corti, B.; Bull, F. (BioMed Central Ltd, 2013)
Background: Studies repeatedly highlight associations between the built environment and physical activity, particularly walking. Fewer studies have examined associations with cardiometabolic risk factors, with associations with obesity inconsistent and scarce evidence examining associations with other cardiometabolic risk factors. We aim to investigate the association between neighborhood walkability and the prevalence of obesity, hypertension, hypercholesterolaemia, and type-2 diabetes mellitus. Methods. Cross-sectional study of 5,970 adults in Western Australia. Walkability was measured objectively for a 1,600 m and 800 m neighborhood buffer. Logistic regression was used to assess associations overall and by sex, adjusting for socio-demographic factors. Mediation by physical activity and sedentary behavior was investigated. Results: Individuals living in high compared with less walkable areas were less likely to be obese (1,600 m OR: 0.84, 95% CI: 0.7 to 1; 800 m OR: 0.75, 95% CI: 0.62 to 0.9) and had lower odds of type-2 diabetes mellitus at the 800 m buffer (800 m OR: 0.69, 95% CI: 0.51 to 0.93). There was little evidence for an association between walkability and hypertension or hypercholesterolaemia. The only significant evidence of any difference in the associations in men and women was a stronger association with type-2 diabetes mellitus at the 800 m buffer in men. Associations with obesity and diabetes attenuated when additionally adjusting for physical activity and sedentary behavior but the overall association with obesity remained significant at the 800 m buffer (800 m OR: 0.78, 95% CI: 0.64 to 0.96). Conclusions: A protective association between neighborhood walkability and obesity was observed. Neighborhood walkability may also be protective of type-2 diabetes mellitus, particularly in men. No association with hypertension or hypercholesterolaemia was found. This warrants further investigation. Findings contribute towards the accumulating evidence that city planning and policy related strategies aimed at creating supportive environments could play an important role in the prevention of chronic diseases. © 2013 Müller-Riemenschneider et al.; licensee BioMed Central Ltd.